A contribution to the study of seismic risks in Ecuador - Maruri Díaz, Raúl (Revista Universidad de Guayaquil, 1985)
A probabilistic method is presented to obtain the maximum expected acceleration at any site in the country, with a given level of exceedance probability. For this purpose, the identification of source areas in the zone is discussed. A particular site is studied and a design spectrum is recommended.